Naturally Occurring Resistance-Associated Variants to Hepatitis C Virus Direct-Acting Antiviral Agents in Treatment-Naive HCV Genotype 6a-Infected Patients. (15th October 2017) - Li, Zhanyi; Liu, Ying; Zhang, Ying; Shao, Xiaoqiong; Luo, Qiumin; Guo, Xiaoyan; Lin, Guoli; Cai, Qingxian; Zhao, Zhixin; Chong, Yutian
Abstract : Background and Objective . The direct-acting antiviral agents (DAAs) antiviral therapy has drastically improved the prognosis of hepatitis C virus (HCV) patients. However, the viral drug resistance-associated variants (RAVs) can limit the efficacy of DAAs. For the HCV-6a is not the predominant prevalent genotype; the data on the prevalence of naturally occurring RAVs in it is scarce. Our study aims to assess the prevalence of RAVs in treatment-naive HCV-6a patients. Methods . Nested PCR assays were performed on 95 HCV-6a patients to amplify HCV viral regions of NS3, NS5A, and NS5B. Results . In NS3/4A region, we detected Q80K in 95.5% isolates (84/88) and D168E in 2.3% isolates (2/88). In NS5A region, we detected Q30R in 93.2% isolates (82/88), L31M in 4.6% isolates (4/88), and H58P in 6.8% isolates (6/88). In NS5B region, we detected A15G in 2.3% isolates (2/88), S96T in 1.1% isolates (1/88), and S282T in 20.7% isolates (17/88) and we detected I482L in 100% isolates (4/4), V494A in 50% isolates (2/4), and V499A in 100% isolates (4/4). Conclusions . RAVs to DAAs preexist in treatment-naive HCV-6a patients. Further studies should address the issue of the impact of RAVs in response to DAA therapies for HCV-6a patients.